Comparison of Reflective Thinking through Project Based Learning and Differentiated Instruction in Islamic Religious Education Based on Minangkabau Ethnography - Herawati, Susi; Ramli, Syahrur; Susrizal, Silvia; Akbar, M Ravi; Delvica, Ghusti (Hikmah, 2025)
Low reflective thinking skills and a lack of understanding of local values among students in Islamic Religious Education are problems at State Senior High School 1 Lintau. Theoretical learning makes it difficult for students to relate religious teachings to the ethnographic culture of Minangkabau. This study aims to compare the effectiveness of project-based learning and differentiated learning models in improving students' reflective thinking skills in integrated Islamic Education lessons incorporating Keminangkabau ethnography. The study used a quantitative comparative approach through an experiment involving 158 students and 4 educators. Data were collected through questionnaires and interviews. The results indicate that the differentiated learning model is more effective in enhancing self-awareness, reflection in action, and future planning. Meanwhile, the project-based model is superior in fostering social reflection. These findings highlight the importance of selecting appropriate learning models to develop reflective skills and strengthen understanding of local values, thereby making Islamic Education more meaningful and contextual.